2018
DOI: 10.1021/acs.est.8b04280
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Use and Transition Trends of Rural Household Energy in Mainland China

Abstract: Household energy use is an important aspect of environmental pollution and sustainable development. From a nationwide residential energy survey, this study revealed that household fuel “stacking”-mixed use of multiple fuels-is becoming noticeable over the 20 years from 1992 to 2012, particularly in northern China where space heating is needed in the winter. Approximately 28% of rural households used only one single energy type in 1992, whereas the percentage declined to merely 11% in 2012. The number of energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 39 publications
4
92
1
Order By: Relevance
“…Lelieveld et al (2015) 2 reported that a total of 434,000 premature deaths, which was ~32% in terms of the relative contribution, were attributable to PM 2.5 and O 3 originating from residential emissions in 2010 in China. Considering that the contribution from residential sources to O 3 precursors was much smaller than that from other sectors 24 , and that residential emissions in China were predominantly from rural areas 3,25 , this value is higher than our estimate. This difference can be partially explained by the difference in emission inventories.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Lelieveld et al (2015) 2 reported that a total of 434,000 premature deaths, which was ~32% in terms of the relative contribution, were attributable to PM 2.5 and O 3 originating from residential emissions in 2010 in China. Considering that the contribution from residential sources to O 3 precursors was much smaller than that from other sectors 24 , and that residential emissions in China were predominantly from rural areas 3,25 , this value is higher than our estimate. This difference can be partially explained by the difference in emission inventories.…”
Section: Resultscontrasting
confidence: 75%
“…This is because the emission factors (EFs, quantities of air pollutants emitted per unit of fuel consumed) for extensively used solid fuels in this sector are very high. According to the latest estimation, 27% primary PM 2.5 (particulate matter with an aerodynamic diameter less than 2.5 μm) and 51% BC (black carbon) emissions in mainland China were from the residential sector in 2014, and nearly 80% was from rural areas 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of access to clean fuels and technologies is due primarily to poverty, and a lack of infrastructure and resources required to deliver and maintain alternative energy sources [27,38]. Even in China, where a rapid transition in residential energy from solid fuels to electricity has occurred in recent decades, the transition tends to lag in rural areas, and transitions are incomplete, with “stacked energy” use being normative (i.e., mixed use of multiple energy) [40]. In 2012, despite introductions of cleaner fuels, 85% of households in China used some form of biomass fuel for heating [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, these improvements were primarily due to urbanization and increased incomes rather than specific policies (Zhao et al., 2018). New policies focusing on residential solid fuels are required because residential solid fuels are still widely used for heating (S. Tao et al., 2018; Zhu et al., 2018), urbanization and income growth are projected to slow (L. Jiang & O'Neill, 2017), and stacking clean fuels with solid fuels is still persistent (Barrington‐Leigh et al., 2019; Zhu et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Solid fuels accounted for 80% of the total fuel consumption by energy in rural households in the PRD in 2017 (X. Jiang et al., 2015). We simulated a 50% transition from solid fuels to liquefied petroleum gas (LPG) outside the GBA by reducing residential emissions from solid fuel use by 50% (RES) as being representative of a partial transition under continued fuel stacking (Barrington‐Leigh et al., 2019; Carter et al., 2019; S. Tao et al., 2018; Zhu et al., 2018).…”
Section: Methodsmentioning
confidence: 99%